Integrating Life Skills and Social Values Through Physical Education and Sport for Positive Youth Development in Indonesia: A Systematic Review - Triansyah, Andika (Jurnal Pendidikan Progresif, 2025)
Integrating Life Skills and Social Values Through Physical Education and Sport for Positive Youth Development in Indonesia: A Systematic Review. Objective: Positive youth development (PYD) through physical education and sports is important in building a healthy, active, and superior young generation in Indonesia. This systematic review aims to determine the effectiveness of integrating life skills and social values in sports to improve PYD in Indonesia. The program is based on intentionally structured positive youth development so that teachers or coaches can develop exercises relevant to the needs of students or athletes to transfer life skills and social values to different aspects of life. Methods: Literature searches were conducted using the Scopus database, and the search strategy was using PRISMA guidelines. Of the 2,597 articles screened, five articles met the inclusion criteria. This study contains information about PYD through physical education and sports learning in Indonesia, with the research population spread across schools or sports clubs. Findings: The results of this review show that the integration of life skills and social value components carried out in adolescents through sports activities and physical education is positively correlated with an increase in positive adolescent development. The results of the study also show that life skills education programs have the potential to protect children from possible negative influences and as a way to maximize the development of adolescents towards a brighter future. Conclusion: The review concludes that integrating life skills and social values through physical education and sport effectively supports PYD in Indonesia. In addition, it is important to conduct consistent research to generate new knowledge about the potential implementation of the integration of life skills and social values through sport to support PYD in Indonesia. However, further research can be expanded by linking the contribution of the PYD to efforts to support educational sustainable development goals through physical education and sports.Keywords: life skills, social values, positive youth development, physical education, sports.